Композицiйнi сцинтилятори та особливостi їх радiацiйної стiйкостi - Krech, A. V.; Galunov, N. Z. (Publishing house "Academperiodika", 2018)
Nowadays, composite scintillators find applications in a growing number of tasks dealing with the detection of ionizing radiation. They have several advantages in comparison with other scintillation materials. With the emergence of a new generation of accelerators, the radiation load on detectors is significantly increased. Therefore, the development of materials with high radiation resistance for radiation detectors becomes an important task. We propose to apply composite scintillators as radiation-resistant materials. The most important factor is that irradiation can significantly modify the characteristics of a scintillation material. The aim of this work was to study the specific features of possible radiation-induced damages and transformations in composite scintillators under the action of ionizing radiation. A comparative analysis of the relative light yield, transmittance, and luminescence spectra, as well as their dependences on the accumulated dose, is carried out for various composite scintillators containing grains of organic or inorganic single crystals, such as Gd2SiO5:Ce, Gd2Si2O7:Ce, Al2O3 :Ti, Y2SiO5:Ce, and Y3Al5O12:Ce. Probable mechanisms of radiation-induced changes occurring in scintillators under irradiation are proposed, and the influence of those processes on the radiation resistance of composite scintillators is analyzed.